2006
DOI: 10.1105/tpc.105.039404
|View full text |Cite
|
Sign up to set email alerts
|

Tocopherols Play a Crucial Role in Low-Temperature Adaptation and Phloem Loading in Arabidopsis  

Abstract: To test whether tocopherols (vitamin E) are essential in the protection against oxidative stress in plants, a series of Arabidopsis thaliana vitamin E (vte) biosynthetic mutants that accumulate different types and levels of tocopherols and pathway intermediates were analyzed under abiotic stress. Surprisingly subtle differences were observed between the tocopheroldeficient vte2 mutant and the wild type during high-light, salinity, and drought stresses. However, vte2, and to a lesser extent vte1, exhibited dram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
286
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(304 citation statements)
references
References 91 publications
15
286
0
2
Order By: Relevance
“…It is not understood how a lack of tocopherol leads to ectopic callose deposition. However, this function is conserved in potato (Solanum tuberosum) and Arabidopsis (Arabidopsis thaliana), as plants deficient for the Sxd1 orthologous gene show a similar callose-deposition and carbohydrateaccumulation phenotype (Hofius et al, 2004;Maeda et al, 2006).…”
Section: Suc Entry Into a Veinmentioning
confidence: 99%
“…It is not understood how a lack of tocopherol leads to ectopic callose deposition. However, this function is conserved in potato (Solanum tuberosum) and Arabidopsis (Arabidopsis thaliana), as plants deficient for the Sxd1 orthologous gene show a similar callose-deposition and carbohydrateaccumulation phenotype (Hofius et al, 2004;Maeda et al, 2006).…”
Section: Suc Entry Into a Veinmentioning
confidence: 99%
“…While EDTA can lead to cell damage 30 , several groups have used this method and observed no adverse effect of EDTA concentrations from 10 mM to 20 mM on the cell ultrastructure or on phloem loading and transport 5,24 . To reduce any damaging effect as well as interference of EDTA with chromatography and gel electrophoresis, plants are moved into water after 1 h and only the later part of the exudate is used 14 .…”
Section: Edta Chelates Camentioning
confidence: 99%
“…Protection of thylakoid membrane lipids against peroxidative damage is a function that is traditionally attributed to vitamin E (Fryer, 1992), although alternative functions have been suggested for vitamin E (Maeda et al, 2006;Munné-Bosch et al, 2007). Thus, unbound zeaxanthin in ch1 thylakoid membranes could fulfill a protective function similar to that of vitamin E. A previous study has shown that zeaxanthin and vitamin E are functionally redundant (Havaux et al, 2005), and this is supported here by the similarity of the phenotypes obtained by suppression of zeaxanthin or tocopherols in ch1.…”
Section: Zeaxanthin and Vitamin E Protect Lipids In An Additive Mannermentioning
confidence: 99%
“…The vte1 Arabidopsis mutant is deficient in tocopherol and accumulates the tocopherol precursor 2,3-dimethyl-phytyl-1,4-benzoquinol (DMPBQ; Maeda et al, 2006). We designed a double mutant, ch1 vte1, deficient in vitamin E, and a triple mutant, ch1 vte1 npq1, deficient in both vitamin E and zeaxanthin.…”
Section: Photoinhibition Of Psii Is Not Enhanced In the Ch1 Npq1 Doubmentioning
confidence: 99%